Tracing Productivity Growth Channels in the UK - Garcia-Macia, Daniel (IMF Working Papers; Working Paper ;, 2021)
What drove the UK productivity slowdown post-GFC, and how is the post-Covid recovery expected to differ? This paper traces the sources of TFP growth in the UK over the last two decades through the lens of a structural model of innovation, using registry data on the universe of firms. The dominant innovation source in the pre-GFC decade were improvements by incumbent firms on their own products, whereas creation of new varieties by entrants took a leading role post-GFC. In the Covid recovery, survey data suggests that creative destruction (i.e., innovation replacing other firms' products) is expected to gain importance. This emphasizes the need for growth policies that facilitate labor and capital reallocation across firms, in addition to R and D support.